2008
DOI: 10.1182/blood-2007-12-130534
|View full text |Cite
|
Sign up to set email alerts
|

Graft-versus-host disease causes failure of donor hematopoiesis and lymphopoiesis in interferon-γ receptor-deficient hosts

Abstract: The immunopathologic condition known as graft-versus-host disease (GVHD) results from a type I T-cell process. However, a prototypical type I cytokine, interferon-␥ (IFN-␥), can protect against several manifestations of GVHD in recipients of major histocompatibility complex (MHC)-mismatched hematopoietic cells. We transplanted hematopoietic cells from C3H.SW donors in wild-type (wt) and IFN-␥-receptor-deficient (IFN-␥RKO) MHCmatched C57BL/6 recipients. In IFN-␥RKO recipients, host cells were unresponsive to IF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 46 publications
(59 reference statements)
3
46
1
Order By: Relevance
“…28 More recently, the same group suggested that IFN␥ produced by alloreactive T cells may cause a severe graft-versus-host reaction, responsible for the lymphopenia associated with GVHD. 29 These insights may explain the observations made in the present work: rsTreg may have a preferential suppressive effect on alloreactive T cells, leading to a qualitative as well as a quantitative improvement in immune reconstitution. The decrease in the fulminant alloactivation may lead to better survival of immune cells as well as promotion of a more "benevolent" cytokine environment.…”
Section: Discussionsupporting
confidence: 69%
“…28 More recently, the same group suggested that IFN␥ produced by alloreactive T cells may cause a severe graft-versus-host reaction, responsible for the lymphopenia associated with GVHD. 29 These insights may explain the observations made in the present work: rsTreg may have a preferential suppressive effect on alloreactive T cells, leading to a qualitative as well as a quantitative improvement in immune reconstitution. The decrease in the fulminant alloactivation may lead to better survival of immune cells as well as promotion of a more "benevolent" cytokine environment.…”
Section: Discussionsupporting
confidence: 69%
“…[12][13][14][15] In fact, IFN-g neutralization improves the in vitro capacity of hematopoietic progenitors from patients with aplastic anemia. 36 Furthermore, IFN-g also plays an important role in the pathogenesis of graft-versus-host disease 37 and disease progression of chronic myeloid leukemia. 38 Our study suggests that the negative impact of IFN-g on HSC proliferation contributes to the impaired hematopoietic function in multiple human diseases, and we speculate that repression of IFN-g signaling could alleviate the hematopoietic suppression in patients with chronic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…33,41,42 Of note, the IL-17 produced after transplantation in these systems is concurrent with other Th1 cytokines (rather than in isolation of) and is predominantly from CD8 ϩ T cells, suggesting that acute GVHD is associated with T-cell differentiation that is not exclusive to Th1 or Th17 pathways, even at a cellular level. In contrast, the role of specific T-cell differentiation pathways on fibrosis after BMT (ie, scleroderma) is not well defined.…”
Section: Socs3 Regulates Gvhd 293mentioning
confidence: 99%